What Are the Determinants of Employability for Vocational Graduates in Jakarta: The Role of Curriculum, Internships, Family Support, and Women's Gender Perspectives? - Agung Kwartama (WISE Pendidikan Indonesia, 2026)
This study explores the factors influencing employability for vocational higher education graduates in Jakarta, focusing on industry-based curriculum, internships, family support, and gender. Using a quantitative approach, Partial Least Squares Structural Equation Modeling (PLS-SEM) and Necessary Condition Analysis (NCA) were employed to analyze the relationships between these variables. Data were gathered through a survey of vocational graduates using purposive sampling. Results show that industry-based curriculum, internship experience, educational infrastructure, campus environment, and family support significantly contribute to employability. The study emphasizes the importance of integrating industry practices into education and providing strong family support, especially for women. This research presents a novel model that combines these factors, offering insights for improving vocational education and supporting female graduates in a competitive labor market. Strategies such as strengthening the curriculum, enhancing internship programs, and ensuring gender-sensitive support structures are essential for improving employability. This study contributes to employability literature by providing a comprehensive framework that can guide educational reforms, particularly focusing on gender equality and practical experience.